2009
DOI: 10.1152/ajprenal.90629.2008
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β upregulation drives tertiary lymphoid organ formation and kidney dysfunction in calcineurin A-α heterozygous mice

Abstract: Calcineurin is an important intracellular signaling molecule which can be inhibited by cyclosporin resulting in immune suppression and nephrotoxicity. Previously, we reported that homozygous loss of the alpha isoform of calcineurin impairs kidney development and function and mimics many features of cyclosporin nephrotoxicity. However, early lethality of null mice prevented further study of renal changes. Alternatively, we examined aged heterozygous (CnAalpha(+/-)) mice. In addition to renal dysfunction and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…TLOs contained all of the essential elements for a local immune response and thus might play a role in IgAN progression (23,29,30). Kelly et al revealed that renal TLO neogenesis was associated with matrix accumulation and loss of renal function in a mouse model (31). In our study, we found that high-grade TLOs were significantly associated with an elevated level of serum creatinine and severe glomerular, interstitial, and arterial lesions.…”
Section: Discussionsupporting
confidence: 57%
“…TLOs contained all of the essential elements for a local immune response and thus might play a role in IgAN progression (23,29,30). Kelly et al revealed that renal TLO neogenesis was associated with matrix accumulation and loss of renal function in a mouse model (31). In our study, we found that high-grade TLOs were significantly associated with an elevated level of serum creatinine and severe glomerular, interstitial, and arterial lesions.…”
Section: Discussionsupporting
confidence: 57%
“…The histological findings of renal TLO formed by infiltrating CD20+ and CD4+ cells support the hypothesis of T helper involvement in physiopathology of IgG4-RD [ 10 ]. The high urinary excretion rate of the active form of TGF-β1 measured in our patient is reported to be crucial for maintaining TLO structure and CD4+ cells activation and plays a role in chronic inflammation and renal fibrosis [ 11 ].…”
Section: Discussionsupporting
confidence: 68%
“…The increase in spleen size is likely due to an expansion of B cells and stromal cells as we reported previously in aged CnAα+/− mice [21]. It is unclear what cell type is responsible for changes in the spleen or if there are any significant phenotypic consequences as a result.…”
Section: Discussionmentioning
confidence: 57%